PENERAPAN PEMBELAJARAN PAI BERBASIS DIGITAL LEARNING DI SMP ISLAM PARLAUNGAN WARU SIDOARJO - Milatul hasanah; Amir Bandar Abdul Majid; Masfufah (Almarhalah: Jurnal Pendidikan Islam, 2024)
This research aims to examine the application of digital-based learning in increasing student creativity at SMP Islam Parlaungan Waru Sidoarjo, Sidoarjo. This research is qualitative research, while data collection uses observation, interviews and documentation methods. The research results show that PAI teachers in delivering lesson material in the classroom use digital media such as PowerPoint, learning videos, and use smartphones as learning aids. By using digital media in the teaching and learning process, it can be concluded that, one of the teacher's methods is to enliven the class atmosphere so that discussions occur between students, making it easier for teachers to convey the material and students easily understanding the material. PAI subject teachers use digital media in their learning by displaying PowerPoint slides and interesting learning videos. By using digital media, the teaching and learning process becomes more effective and efficient. The use of PPT and learning videos can help students understand the material better and spark creative ideas, while smartphones facilitate wider access to information and interaction. Thus, implementing digital-based learning at SMP Islam Parlaungan Waru Sidoarjo can be an effective strategy for increasing student creativity, which can support more active and innovative learning.